2017
DOI: 10.1111/jce.13372
|View full text |Cite
|
Sign up to set email alerts
|

Second‐generation cryoballoon ablation for treatment of persistent atrial fibrillation: Three‐year outcome and predictors of recurrence after a single procedure

Abstract: Sinus rhythm was maintained in a substantial proportion of patients even 3 years after CB ablation. Patients with a nonenlarged left atrium and short AF history had the best outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
(87 reference statements)
3
28
0
Order By: Relevance
“…According to our experience with CB ablation, a larger common ostium is a significant drawback for a good occlusion, circumferential tissue contact and lesion formation. We also determined that LA area is a significant predictor of outcome, being in line with recent data . Enlarged left atria may be accompanied by LA remodeling and interstitial fibrosis, which could explain the increased incidence of AFLAT recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our experience with CB ablation, a larger common ostium is a significant drawback for a good occlusion, circumferential tissue contact and lesion formation. We also determined that LA area is a significant predictor of outcome, being in line with recent data . Enlarged left atria may be accompanied by LA remodeling and interstitial fibrosis, which could explain the increased incidence of AFLAT recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we want to point out that we analyzed only patients undergoing PVI alone in this trial. Some of these patients have been previously reported (60 patients with relatively small left atria and “early persistent” AF as well as 63 patients—all of them with a LA area more than 20 cm 2 , considered to be enlarged—undergoing CB‐PVI compared with RF‐PVI) . Although PVI with CB‐Adv is effective and leads to both PVI and LA substrate modification, the use of CB‐Adv might be insufficient in patients with an enlarged left atrium due to larger residual substrate areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the target of the procedure is defined by effective and permanent PVI, the ablation can be carried out independently of the presenting rhythm, since the restoration of SR during the ablation is not a goal in itself; still, in our experience, this phenomenon occurred in a relevant number of cases (3.7%), showing a high mid‐term success rate in terms of AF recurrence both at 1 year (91.9%) and at 2 year follow‐up (86.5%) in patients in whom termination of AF occurred during cryo‐applications. This result may carry a specific meaning when compared to previous large studies on CB‐A outcomes, eventually implicating that the pulmonary venous electrical activity might have been the main driver for fibrillation in these patients and therefore properly treated with CB‐A PVI. Still, it cannot be excluded that termination of AF simply identifies patients who have lesser electroanatomical remodeling and then more likely to remain in SR.…”
Section: Discussionmentioning
confidence: 62%
“…Of note, 10 patients (18.9%) in our case group were affected by persistent AF, showing a success rate of 88.9% at 1 year follow‐up; given the borderline LA dimensions in our case group (mean LA diameter 40.5 ± 7.5 mm) and particularly in this subgroup of patients (indexed LA diameter 26.5 mm/mq), these data may further confirm and highlight that the most relevant substrate for AF in our case group was probably confined to PV potentials. The importance of LA dimensions in the settings of CB‐A has been recently confirmed by Akkaya et al, as they showed that left atrial area >21 cm 2 was a significant predictor of recurrence in a population of 101 patients undergoing CB‐A with second‐generation CB. Furthermore, in a recent work from Gramlich et al, the degree of atrial fibrosis was proved to correlate with the risk of AF recurrence at 1 year follow‐up after CB‐A in 60 patients with persistent AF, therefore stressing the relevance of possible residual substrate areas besides PVs in those patients with a large extent of low‐voltage areas and more generally of the LA disease.…”
Section: Discussionmentioning
confidence: 83%